GE_GERICHTE P/24284/2017 vom 24. Oktober 2019 - GE Cour de justice (2019)
RECOURS JOINT;DÉCISION D'IRRECEVABILITÉ;IN DUBIO PRO DURIORE;LÉSION CORPORELLE SIMPLE;COMPLICITÉ;TRAITEMENT AMBULATOIRE | CPP.401.al1; CPP.399.al3; CPP.399.al4; CEDH.6.par2; CEDH.32.al1; CP.123.al1; CP.25; CP.47; CP.56; CP.63; CP.63.al3; CPP.126.al2.letb